Physical condition and habits of practice exercise of hunters extremeños - José Martín Gamonales Puerto; Kiko León Guzmán; Jesús Muñoz Jiménez (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Present study analyses the physical condition and the physical-sportive exercise in a random sample of hunters (n=144) in the Extremadura (Spain). Hunting is recognized as a sportive modality by the Board of the CDS (Spanish High Sports Council). In order to know the physical condition levels in hunters group, were used a selection of Eurofit and AFISAL-INEFC tests for adult. Final results show the relation which exist between physical condition and sociodemographic differences, as well as the influence that hunting can have in a healthy lifestyle. Attending to the results, there are differences in the physical condition according to the age of the individuals. Moreover, it shows a relation between the sociodemographic characteristics of the sample and the additional physical-sportive exercises of the different modalities of hunting.